2013
DOI: 10.1101/gad.222380.113
|View full text |Cite
|
Sign up to set email alerts
|

Does the microenvironment influence the cell types of origin for prostate cancer?

Abstract: Despite several recent studies addressing the cells of origin for prostate cancer, there is still considerable discussion in the field regarding the most relevant target populations for transformation. Tissue regeneration studies have pointed to a basal cell origin for mouse and human prostate cancer. In contrast, genetically engineered mouse models demonstrate that cells within both the basal and luminal layers can initiate murine prostate cancer. Based on differences between these two approaches, we propose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 65 publications
2
24
0
Order By: Relevance
“…It is well known that complex interactions regulate immune cells in the tumor microenvironment [26][27][28][29]. Immune system cells infiltrating prostate cancer include cells associated with innate immune response i.e., macrophages [30,31], neutrophils [32], mast cells (MCs) [33][34][35], and natural killer (NK) cells [36], as well as cells associated with an adaptive immune response i.e., T-and B-lymphocytes [37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that complex interactions regulate immune cells in the tumor microenvironment [26][27][28][29]. Immune system cells infiltrating prostate cancer include cells associated with innate immune response i.e., macrophages [30,31], neutrophils [32], mast cells (MCs) [33][34][35], and natural killer (NK) cells [36], as well as cells associated with an adaptive immune response i.e., T-and B-lymphocytes [37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…5 In addition, the ability of inflammation to enhance basal-to-luminal differentiation in vivo 20 suggests that alteration of the tissue microenvironment could influence the cell of origin. 13 Many attempts have been made to identify the cellular origin of canine PC but remain inconclusive thus far. Within the prostatic epithelium, basal and luminal cells can be distinguished on the basis of their localization, morphology, and phenotypic features.…”
mentioning
confidence: 99%
“…7 Microcephalin is involved in the DNA-damage response and has been linked to tumor formation and cancer AGR2 is developmentally regulated initially discovered as an estrogen-responsive gene in breast cancer cell lines currently linked to tumors with poor outcome. 10 With regard to the influence of the microenvironment on cells and how changes in such microenvironments 11 could lead to phenotypic progression and cancer transformation, 12 analysis showed that alterations in external factors, such as the pH of a tissue, could trigger cellular changes 13 and regulate cell transformation. 14 An acidic environment (pH 6.5-6.9 compared with pH 7.2-7.4) could cause degradation of the extracellular matrix (ECM) and lead to the secretion of VEGF, as well as to angiogenesis, which can correlate with tumor transformation and cellular invasion ( Figure 4).…”
Section: Malignant Transformation: From a Normal To A Cancerous Phenomentioning
confidence: 99%